2019
DOI: 10.7717/peerj.7455
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet disinfection impacts the microbial community composition and function of treated wastewater effluent and the receiving urban river

Abstract: Background In the United States, an estimated 14,748 wastewater treatment plants (WWTPs) provide wastewater collection, treatment, and disposal service to more than 230 million people. The quality of treated wastewater is often assessed by the presence or absence of fecal indicator bacteria. UV disinfection of wastewater is a common final treatment step used by many wastewater treatment plants in order to reduce fecal coliform bacteria and other pathogens; however, its potential impacts on the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 82 publications
2
5
1
Order By: Relevance
“…For the diversity index Shannon, it was found that with the increase of UV radiation time, only the UV5 group was greater than UV0, suggesting that UV irradiation had some reducing effect on microbial diversity, in line with the findings of (Kauser et al, 2019). It is noteworthy that the Shannon index was overall lower than that of 5 min at 5 to 180 min of UV irradiation.…”
Section: Microbial Relative Abundance and Diversitysupporting
confidence: 77%
See 1 more Smart Citation
“…For the diversity index Shannon, it was found that with the increase of UV radiation time, only the UV5 group was greater than UV0, suggesting that UV irradiation had some reducing effect on microbial diversity, in line with the findings of (Kauser et al, 2019). It is noteworthy that the Shannon index was overall lower than that of 5 min at 5 to 180 min of UV irradiation.…”
Section: Microbial Relative Abundance and Diversitysupporting
confidence: 77%
“…The KEGG PATHWAY database includes various metabolic pathways and is graphically plotted using Origin 8.6 software. UV irradiation has a facilitative effect on specific bacterial relative abundances (Kauser et al, 2019).…”
Section: S Rrna Gene Function Predictionmentioning
confidence: 99%
“…Molecular DNA-based methods analyze the microbial community without the need for cultivation and, as UV irradiation causes DNA lesions and reduces the number of amplifiable target templates in the PCR reaction 13,19 , amplicon-based methods can describe which types of bacteria and genes are affected by UV [20][21][22] . Microbial inactivation of Pseudomonas aeruginosa and Enterococcus faecium by UV was assessed by cultivation and quantitative PCR (qPCR) 19 and impact of UV on adenovirus concentrations were measured by cell culture infectivity and long-range PCR with subsequent qPCR 23 .…”
Section: Introductionmentioning
confidence: 99%
“…An initial study using 16s rRNA gene amplicon sequencing conducted by Nocker et al 21 showed how some phyla of bacteria were affected by a single dose of UV in a full-scale drinking water treatment plant. The approach of using 16S rRNA gene amplicon sequencing has been used to observe changes in the bacterial community for UV wastewater disinfection 22 and UV irradiation of marine water 28 .…”
Section: Introductionmentioning
confidence: 99%
“…Cl, ClO 2 , PAA) or physical treatments (e.g. UV) [14]. Chlorine dioxide (ClO 2 ) has several advantages: it is a better bactericide and virucide than sodium hypochlorite and chlorine, in relationship to its greater oxidative capacity [15].…”
mentioning
confidence: 99%